hydrochemistry Evaluation of Groundwater Suitability for consumption in Yaychi area (Southwest Kirkuk city - North Iraq) - Al-Kubaisi, Qusai Y.; Khorsheed, Sabah Ahmed (Iraqi Journal of Science, 2018)
Groundwater suitability for consumption in the Yaychi area is determined by analyzing groundwater samples of 21 wells distributed in the area, for dry period which begin from May to October 2016 and wet period begin from October 2016 to May 2017. Results indicated that the temperature (T °C) have normal values and thewater of low alkaline and excessively mineralized, while most of these samples, for both periods, are slightly – brackish water. The mean ion concentrations for two periods indicates that all major and secondary ions are higher than water quality standards for drinking purposes according to World Health Organization (WQI) andIraqi Standard (IQS) except for K and Cl ions. The water in the study area is classified as very hard. Kurolov formula shows the presence of three predominant salts MgSO4, Na2SO4 and CaSO4, and the water origin in the area is meteoric water. The predominated of water types are " earth alkaline water with increased portionsof alkalis with prevailing sulfate and chloride" and "Normal earth alkaline water with prevailing sulphate or chloride". After comparing the ionic concentrations with the water quality standards for different purposes, it was found that groundwater in the area is unsuitable for human drinking, but it's suitable for building and livestock and for growing most types of crops, it is also suitable for irrigation purposes depending on the sodium adsorption ratio (SAR), Soluble Sodium Percentage(Na%) and the Residual Sodium Carbonate (RSC), and unfit for irrigation according to Magnesium Adsorption Ratio(MAR) index. The water in the study area is devoid of heavy metal pollution except (Fe), (Pb) which are shown in water of some wells.